An analysis of the 1969 Bureau of Public Schools achievement test in Philippine history and government and current events - Mejorada, Adela F. 1916- (s.n.], 1971)
An analysis of the 1969 Bureau of Public Schools achievement test in Philippine History and Government and Current Events administered to all sophomore students throughout the Philippines was done on April 10, 1969, with the primary purpose of comparing the skills, abilities, knowledges and understandings of students in mother and barrio high schools throughout the Philippines. The reliability of the said test was determined in this study.